Experiences of participating in a problem-solving intervention with workplace involvement in Swedish primary health care: a qualitative study from rehabilitation coordinator's, employee's, and manager's perspectives - Ida Karlsson; Lydia Kwak; Iben Axén; Gunnar Bergström; Ute Bültmann; Kristina Holmgren; Elisabeth Björk Brämberg (BMC, 2023)
Abstract Background Work-directed interventions that include problem-solving can reduce the number of sickness absence days. The effect of combining a problem-solving intervention with involvement of the employer is currently being tested in primary care in Sweden for employees on sickness absence due to common mental disorders (PROSA trial). The current study is part of the PROSA trial and has a two-fold aim: 1) to explore the experiences of participating in a problem-solving intervention with workplace involvement aimed at reducing sickness absence in employees with common mental disorders, delivered in Swedish primary health care, and 2) to identify facilitators of and barriers to participate in the intervention. Both aims targeted rehabilitation coordinators, employees on sickness absence, and first-line managers. Methods Data were collected from semi-structured interviews with participants from the PROSA intervention group; rehabilitation coordinators (n = 8), employees (n = 13), and first-line managers (n = 8). Content analysis was used to analyse the data and the Consolidated Framework for Implementation Research was used to group the data according to four contextual domains. One theme describing the participation experiences was established for each domain. Facilitators and barriers for each domain and stakeholder group were identified. Results The stakeholders experienced the intervention as supportive in identifying problems and solutions and enabling a dialogue between them. However, the intervention was considered demanding and good relationships between the stakeholders were needed. Facilitating factors were the manual and work sheets which the coordinators were provided with, and the manager being involved early in the return-to-work process. Barriers were the number of on-site meetings, disagreements and conflicts between employees and first-line managers, and symptom severity. Conclusions Seeing the workplace as an integral part of the intervention by always conducting a three-part meeting enabled a dialogue that can be used to identify and address disagreements, to explain CMD symptoms, and how these can be handled at the workplace. We suggest allocating time towards developing good relationships, provide RCs with training in handling disagreements, and additional knowledge about factors in the employee's psychosocial work environment that can impair or promote health to increase the RCs ability to support the employee and manager.